Effects of heavy metals on eggs and larvae of horseshoe crab Tachypleus gigas (Muller 1785) - Nelson, Bryan Raveen (Terengganu: Universiti Malaysia Terengganu, 2013)
Horseshoe crabs inhabit coastal waters of Peninsular Malaysia, with nesting activity observed at Pantai Balok, Pahang. Pantai Balok is exposed to a variety of human threats such as boating and leisure activities which contribute to metal contamination. Hatching success of horseshoe crab eggs could be affected because eggs were left to mature buried in sediments during mating periods.